ARTIFICIAL INTELLIGENCE AND MACHINE LEARNING IN PERSONALISATION MARKETING: A LITERATURE REVIEW - Alim Hardiansyah; Loso Judijanto (Review of International Economy and Finance, 2025)
Artificial Intelligence (AI) and Machine Learning (ML) have rapidly developed in supporting personalised marketing strategies. This study focuses on a literature review to explore the role of AI and ML in enhancing the effectiveness of personalisation, such as big data processing, consumer behaviour analysis, and the provision of relevant recommendations. The analysis results indicate that these technologies can enhance customer experience and marketing campaign efficiency. However, challenges such as data privacy, ethics, and significant technological investments remain key concerns in their implementation. This study concludes that AI and ML offer great potential for data- driven personalisation marketing, while requiring ethical and adaptive approaches to maximise their benefits sustainably.